Memahami Dinamika Harga Saham melalui Kinerja Keuangan dan Skala Perusahaan, Dengan Peran Kebijakan Dividen sebagai Variabel Pengendali pada Perusahaan Industri Dasar dan Kimia di Indonesia - Satria, Nur Ahmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
The dynamics of stock prices is a very important aspect of the capital market. The price of a company's stock is influenced by many factors, including the company's financial performance and the size of the company. In addition, dividend policy is also considered as an important variable in controlling stock prices. However, there is not yet a strong consensus about the extent of the role of dividend policy in moderating the relationship between financial performance and company scale and stock prices. This study aims to understand in depth the dynamics of stock prices through analysis of financial performance and company scale, with particular emphasis on the role of dividend policy as a controlling variable. We aim to identify the extent to which financial performance and firm size affect stock prices, and to what extent dividend policy can moderate this relationship. This study uses a quantitative approach with regression analysis as the main method. Historical data on financial performance, company scale, dividend policy and company stock price will be analyzed for the relevant period. In addition, descriptive statistical analysis and significance test will be used to examine the relationship between these variables. The results of the study show that simultaneously financial performance, company scale, and dividend policy have an effect on stock prices with a contribution value of 72% is a significant finding. It provides a solid understanding of the complexity of the factors that influence stock prices in Chemical and Basic Industry companies in Indonesia. In addition, the finding that dividend policy can act as a moderating factor in increasing stock prices also has important implications. This indicates that company management has an effective tool in managing market perceptions of their stock prices through dividend policy. When used wisely, dividend policy can be a strategic instrument to increase the value of the company in the eyes of investors.